The Effect of Powder Color and Adhesive Visciousness on the Resistance of Sawsuddinary Painting - Octaviani, Wiwi; Yusuf, Muhammad; Karim, Khadijah Aziz; Ayu, Srida Mitra (Jurnal Penelitian Kehutanan BONITA, 2025)
Sawdust is the result of residue from the sawmill industry. Generally, it has no economic value, but ithes selling value when it processed into an artistic work suchas painting made of wood powder. The purpose of this study is to determine the effect of adding adhesive solvents on the resistance of sawdust painting. Through the experiment using a 2  factorial completely randomized design, namely powder color and water volume. Powder color consists of 2 levels (S1 and S2) and 3 levels of water volume (A1, A2, A3) and repeated 3 times, so that the combination of treatment are 18 paintings with the ANOVA test observation parameters the number of points, shape, and area of damage. Howeveri the results show that the volume of water has an effect on the area of damage, so that the color of the powder is not significant for the effect on all parameters of the observation. The results of the Tukey test, water volume (A3) on the damage area showed has a significant effect. The addition of adhesive solvent affects the resistance of powder painting in terms of the extent of damage, the more solvent is added, the lower of the resistance of powder painting.